Testing Enforcement Strategies in the Field: Legal Threat, Moral Appeal and Social Information - Gerlinde Fellner; Rupert Sausgruber; Christian Traxler (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2009)
We run a large-scale natural field experiment to evaluate alternative strategies to en- force compliance with the law. The experiment varies the text of mailings sent to potential evaders of TV license fees. We find a strong alert effect of mailings, leading to a substantial increase in compliance. Among different mailing conditions a legal threat that stresses a high detection risk has a significant and highly robust deterrent effect. Neither appealing to morals nor imparting information about others' behavior enhances compliance. However, the information condition has a positive effect in municipalities where evasion is believed to be common. Overall, the economic model of crime performs remarkably well in explaining our data.
Keywords: K42; C93; 330; Field experiments; law enforcement; compliance; deterrence